Macrocyclic Peptoids by Selective S-Acylation of Cysteine Esters - Ibrahim, Mohamed A.; Panda, Siva S.; Nhon, Linda; Hamed, Ahmed; El-Feky, Said A.; Katritzky, Alan R. (Synthesis, 2013)
Optimized selective S-acylations of cysteine esters gave intermediates for the synthesis of macrocyclic peptoids by a benzotriazole-based method.
Keywords: acylations; amino acids; macrocycles; heterocycles